Risiko Dehumanisasi pada Crowdfunding sebagai Akses Pendanaan Berbasis Teknologi di Indonesia - Gita Widi Bhawika (Jurnal Sosial Humaniora, 2017)
Crowdfunding is the novel phenomenon. This fundraising based technologyhas increased its popularity since a decade ago. Crowdfunding can helppeople to funding their initiatives without boundaries because it only needinternet connection to ask and give money. It is not necessary to gainrelationship between initiator and funder. Yet, from the conventionalfundraising point of view, it is important to build relationship to increasethe loyal funder who can easily fund the future initiator’s initiatives. Thus,crowdfunding has potential dehumanization risks. This descriptive researchwill discuss about crowdfunding in Indonesia, and its dehumanization risks.Moreover, this paper will describe crowdfunding phenomenon in Indonesiaand also propose the model of crowdfunding’s donor relationshipmanagement to minimize the dehumanization risks.